Treatment-free remission after first-line dasatinib discontinuation in patients with chronic myeloid leukaemia (first-line DADI trial): a single-arm, multicentre, phase 2 trial. Issue 3 (March 2020) - Kimura, Shinya; Imagawa, Jun; Murai, Kazunori; Hino, Masayuki; Kitawaki, Toshio; Okada, Masaya; Tanaka, Hideo; Shindo, Motohiro; Kumagai, Takashi; Ikezoe, Takayuki; Uoshima, Nobuhiko; Sato, Tsutomu; et al.
Summary: Background: A previous dasatinib discontinuation (DADI) trial showed that 31 (49%) of 63 patients with chronic-phase chronic myeloid leukaemia who were treated with second-line or subsequent dasatinib could discontinue the drug safely. However, the safety and efficacy of discontinuing first-line dasatinib remains unclear. In this trial (the first-line DADI trial) we aimed to assess molecular relapse-free survival at 6 months after discontinuation of dasatinib in patients with chronic myeloid leukaemia who had been treated with first-line dasatinib and had maintained deep molecular response for at least 1 year. Methods: The first-line DADI trial was a single-arm, multicentre, phase 2 trial done at 23 hospitals in Japan. Patients with newly diagnosed chronic-phase chronic myeloid leukaemia without hepatosplenomegaly and extramedullary mass, who received at least 24-month dasatinib treatment and had a sustained deep molecular response (defined as BCR-ABL1/ABL1 international scale ≤0·0069% in at least four successive samples spanning a 12 month period) were enrolled. Other eligibility criteria were an age of 15 years or older, an Eastern Cooperative Oncology Group performance status score of 0–2, and no primary organ dysfunction. The primary outcome was molecular relapse-free survival (also known as treatment-free remission) after discontinuation of dasatinib at 6 months and was analysed in all patients who completed the 12-month consolidation phase. Safety was assessed in all patients who received treatment. This study closed early due to accrual and is registered with the UMIN Clinical Trials Registry (UMIN000011099). Findings: Between Sept 20, 2013 and July 12, 2016, 68 patients who had a deep molecular response after receiving first-line dasatinib for at least 24 months were enrolled and assigned to the consolidation phase. Nine patients were excluded during the consolidation phase and one patient was excluded after study completion because of meeting exclusion criteria. 58 patients discontinued dasatinib and were assessed. 32 (55%) of 58 patients had treatment-free remission at 6 months after dasatinib discontinuation, and median follow-up was 23·3 months (IQR 11·7–31·0). Treatment-free remission at 6 months was 55·2% (95% CI 43·7–69·6). No non-haematological adverse events worse than grade 2 occurred before dasatinib discontinuation. The most common haematological adverse event was anaemia (14 [21%] of 68 treated patients); three (4%) of 68 treated patients had grade 3 neutropenia and one (1%) had grade 4 lymphopenia. Interpretation: Our findings suggest that dasatinib could be safely discontinued after first-line treatment in patients with chronic myeloid leukaemia who had received at least 36 months of therapy and sustained deep molecular response; however, further confirmation in larger trials is needed. Funding: Epidemiological and Clinical Research Information Network.